KONSEP MEKANISME PENYELESAIAN SENGKETA MELALUI SMALL CLAIM COURT SUATU STUDI PERBANDINGAN DAN IMPLEMENTASINYA DI INDONESIA - Panjaitan, Hulman (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
The demand of society seeking justice is for simple, speedy, and cost-effective dispute resolution. This is the foundation for the establishment of the principle of justice in Indonesia in accordance with Law Number 48 of 2009 concerning the Judicial Power, namely the principles of simple, speedy, and cost-effective justice. This is due to the fact that dispute resolution through litigation often fails to satisfy the parties involved due to its relatively lengthy process, complexity, and high costs. Meanwhile, dispute resolution outside the court (non-litigation) lacks executive power because it is solely contractual. The mechanism for resolving disputes through the Small Claims Court was initially known and practiced in countries with a common law system, eventually adopted by countries with a civil law system. In Indonesia, it was translated and implemented through the examination of simple lawsuits in accordance with the Supreme Court Regulation of the Republic of Indonesia Number 2 of 2015 concerning Procedures for Filing Simple Lawsuits, as amended and perfected by the Supreme Court Regulation of the Republic of Indonesia Number 4 of 2019 concerning Amendments to the Supreme Court Regulation of the Republic of Indonesia Number 2 of 2015 concerning Procedures for Filing Simple Lawsuits.